The Impact of Macroeconomic Effect and Fiscal Policy on Poverty in Indonesia - Hadi Sumarsono; Ermita Yusida; Suhaili Alma’amun (Jurnal Ekonomi dan Studi Pembangunan, 2022)
Poverty is a problem that must be overcome immediately by a developing country. Therefore, various efforts were made to find factors that significantly affect poverty in order to design an alleviation strategy. This study aims to determine the impact of macroeconomic effect and fiscal policy on poverty poverty in all the Indonesian provinces from 2018 to 2020. The macroeconomic effect proxied by unemployment, Human Development Index (HDI), investment, and economic growth. Besides that, the fiscal policy proxied by social assistance. The data analysis used in this study is panel data. The time-series data used are from 2018 to 2020, and the cross-section data used is from 34 provinces in Indonesia. The model selected in this study is the Fixed Effect Model (FEM). This study found that unemployment had a significant positive effect, and HDI had a significant negative impact on poverty in Indonesia. In contrast, social assistance did not have a significant impact. Simultaneously, unemployment, HDI, and social assistance exert a significant influence.